Breast Feeding And Its Significance In Infant Feeding Practices In India - Belavady Bhavani (Wolters Kluwer Medknow Publications, 1987)
Surveys on breast-feeding practices have revealed a satisfactory situation in many parts of the country. However, adequacy in terms of quality and quantity of breast milk has not been studied much. Reports available indicate secretion of adequate amount of milk by the mother. This however should not be equated with adequacy of nutrients to this growing child. Concentrations of vitamins are low. The immunologica factors, proteins, minerals and calorie content are in the normal ranges observed in milk samples obtained from well-nourished mother. Breast-feeding should be recommended for as long as possible with adequate supplements. This will have a salubrious effect on the infant and help mothers in spacing births of children. Growth of infants fed soley on breast milk is satisfactory during the first 4 to 5 months. Proper time and type of supplements to be recommended for the community in general need to be studied. Effect of work outside the house on the mother and child, if any, has not received the attention it deserves. High priority has to be a corded to this study, in the present context of dynamic change occurring in the country in relation to the working status of women. Indian is considered a developing country and Indians are conservative by nature. Attitude of the community to infant feeding has not change much except in the educated urban elite and a small section of the poor who consider practice among the former as ideal. The concern and anxiety expressed with regard to breast-feeding by health personnel in foreign countries have not evoked the same response in our country. Reasons are many but if any single reason is to be assigned, it is the popularity of breast-feeding in a vast majority of our mothers. This article will highlight the findings of selected surveys on breast-feeding in the context of our present infant and pre-school feeding practices and refers to the quality and quantity of breast milk briefly.